Lymphocyte Transformation Test (LTT) in Allergy to Benznidazole: A Promising Approach - Marques-Mejías, M. Andreína; Cabañas, Rosario; Ramírez, Elena; Domínguez-Ortega, Javier; Fiandor, Ana; Trigo, Elena; Quirce, Santiago; Bellón, Teresa (Frontiers in Pharmacology, 2019)
Benznidazole (Bzn) from the nitroimidazole family and nifurtimox from nitrofurans family, are drugs used as first and second line treatment for acute and chronic phases of Chagas disease (CD). Even though skin re-actions are frequent, confirmed allergy to Bzn is rare, and there are few cases reported in the literature. Since CD treatment is very restrained, the possibility of cross-reactivity between members of the same and other pharmacological families highlights the importance of an adequate diagnosis that allows alternative treatments in CD and other diseases. We report a series of 31 patients (69% women) referred to our Allergy unit with suspected hypersensitivity to Bzn, twenty-three of them with mild reactions and nine of them with severe reactions. LTT with Bzn was performed in 31 patients and in 8 negative controls. LTT was also performed in 25 and 20 of these patients with nifurtimox and Mtn, respectively. Twenty one out of thirty one patients were Bzn prick tested, all negative. We obtained 2/21 positive results on patch tests to Bzn. LTT with Bzn was positive in 22/31 patients (Sensitivity 75.9% and specificity 100%). The test was considered positive with a stimulation index >2. There was a positive result in 7/25 patients for nifurtimox and in 7/20 patients with Mtn. After negative LTT and skin tests, oral provocation was performed in 4/9 patients, all negative. LTT is a safe test that seems to be more useful than skin tests (prick and patch test), particularly in severe reactions, in con-firming delayed hypersensitivity to Bzn and detecting cross reactivity with other imidazoles such as Mtn and reactivity to other drugs like nifurtimox. Tests for these drugs need to be included in the workup of patients with hypersensitivity to Bzn in case they are needed as an alternative treatment for CD or to treat other frequent infectious diseases.